Association of Disability Benefits and/or Litigation With Time to Return to Work After Tibia Shaft Fracture Fixation. Issue 5 (May 2020) - Rehman, Yasir; Jones, Aaron; Madden, Kim; Heels-Ansdell, Diane; Busse, Jason W.
Abstract : Objectives: We explored the association of compensation status with return to work (RTW) after tibial fracture. Methods: Eligible patients were adults with tibial shaft fractures enrolled in the Trial to Re-evaluate Ultrasound in the Treatment of Tibial Fractures. We explored the association between disability benefits and/or litigation and RTW using multivariable discrete interval hazard analysis, adjusting for sex, age, country of residence, smoking status, body mass index, polytrauma, fracture severity, fracture gap, pain severity, and physical functioning. Results: Of 330 eligible patients, 111 (34%) had not returned to full-time work 1-year after surgery. In our adjusted model, receipt of disability benefits and/or involvement in litigation was associated with delayed RTW (HR = 0.71, 95% CI 0.52-0.96). Discussion: Tibial shaft fracture patients receiving disability benefits and/or involved in litigation are less likely to RTW. Abstract : Supplemental Digital Content is available in the text